1996
DOI: 10.1093/hmg/5.1.139
|View full text |Cite
|
Sign up to set email alerts
|

Deletions in Xq28 in Two Boys with Myotubular Myopathy and Abnormal Genital Development Define a New Contiguous Gene Syndrome in a 430 kb Region

Abstract: We have recently described a female patient with myotubular myopathy (MTM1) and an interstitial deletion at Xq28. Characterisation of the deletion allowed us to position the MTM1 gene to a 600 kb region between DXS304 and DXS497. In order to further restrict the region we screened for deletions in a set of 38 patients. We found two overlapping deletions in boys that in addition to MTM1 showed an unexpected abnormal genital development. As the latter phenotype is not found in the other non-deleted MTM1 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
57
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 19 publications
2
57
0
Order By: Relevance
“…It is also hypothesized to be implicated in male genital development. Indeed, myopathic individuals with intragenic mutations of MTM1 have normal sexual development, whereas those with microdeletions of MTM1 extending to the CXorf6 locus have abnormal genitalia (8)(9)(10)(11). Subsequent studies have demonstrated that CXorf6 is mutated in 46,XY disorders of sexual development (46,XY DSD): Fukami et al (12) have identified three nonsense mutations in four individuals with 46,XY DSD including micropenis, bifid scrotum, and penoscrotal hypospadias.…”
Section: Introductionmentioning
confidence: 99%
“…It is also hypothesized to be implicated in male genital development. Indeed, myopathic individuals with intragenic mutations of MTM1 have normal sexual development, whereas those with microdeletions of MTM1 extending to the CXorf6 locus have abnormal genitalia (8)(9)(10)(11). Subsequent studies have demonstrated that CXorf6 is mutated in 46,XY disorders of sexual development (46,XY DSD): Fukami et al (12) have identified three nonsense mutations in four individuals with 46,XY DSD including micropenis, bifid scrotum, and penoscrotal hypospadias.…”
Section: Introductionmentioning
confidence: 99%
“…1 The locus responsible for the disease (MTM1) was mapped to proximal Xq28 by linkage analysis and the candidate region was restricted by analysing recombination events and patients carrying deletions. 2,3 We have recently reported the identification of the MTM1 gene by positional cloning. 4 It encodes a protein (myotubularin) with a putative tyrosine phosphatase domain (PTP).…”
Section: Introductionmentioning
confidence: 99%
“…Four cosmids (ICRF C104-H05147, C104-E03147, C104-B03151 and a Xq28 specific library cosmid Qc3A3) were subcloned as described. 3 Subclones were screened by hybridisation with radioactively labelled cDNAs or oligonucleotides, and by PCR, for the presence of MTM1 exons and further sequenced with exon specific primers. As exons 5 to 8 were not included in our cosmid contig, PCR and long-range PCR from genomic DNA was performed with exonic primers, to clone introns 4, 5, 6, 7 and 8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large deletions including part or the entire upstream MAMLD1 gene cause a contiguous gene syndrome with hypospadias and myotubular myopathy in males. 13 A duplication of exon 10 has been recently described in an affected male. 14 DNM2: Thirteen heterozygous missense changes or in-frame deletions or insertions have been reported with hotspots at position 368, 369, 465, 522, 618 and 619.…”
mentioning
confidence: 99%